Sociological factors of women criminality: a systematic review - Shu, Yen Ang; Geshina Ayu Mat Saat (Penerbit Universiti Kebangsaan Malaysia, 2024)
The number of women prisoners is rising globally, yet many rehabilitation programmes predominantly emphasize the psychological aspects of female inmates. This review underscores the importance of investigating the sociological factors that precede women's criminal behaviours. The systematic review encompassed documents from five databases: Emerald Insights, ERIC, PubMed, SCOPUS, and Web of Science. The inclusion criteria were documents published between 1st January 2018 and 9th July 2024, full-text articles, studies that involved incarcerated women over the age of 18, investigated the social factors that lead women into crime, and studies written in English. The exclusion criteria comprised studies that solely involved male offenders, before 1st January 2018 and after 9th July 2024, unrelated content, duplicates, abstract-only papers, editorials, author responses, theses, books, book chapters, review studies, studies without available full-text, or serials. Out of 11,594 documents, 21 studies were finally selected for review. The sociological factors contributing to women's criminality revolved around family and intimate partner abuse victimization influenced by traditional gender roles, criminal community, as well as financial motivation and the impact of social media. These findings accentuate the importance of rehabilitation programmes addressing sociological factors to meet the unique needs of women offenders. In conclusion, this systematic review provides an in-depth understanding of the sociological factors that led women into crime, serving as important insights to the development of prison interventions.